Back Contact Heterojunction Solar Cells Patterned by Laser Ablation. (August 2016) - Harrison, Samuel; Nos, Oriol; D'Alonzo, Guillaume; Denis, Christine; Coll, Arnau; Munoz, Delfina
Abstract: Back contact heterojunction (IBC-HIT) solar cells is one of the most promising technology for the upcoming generations of high efficiency crystalline-Silicon (c-Si) based photovoltaic modules[1] . However, the industrialization of the IBC-HIT technology is actually constrained by the complexity of the back side cell processing, which usually involves costly and time consuming photolithography steps. CEA-INES is currently developing a method based only on laser ablation for the structuration of IBC-HIT solar cells[2] . Laser ablation is indeed a fast and low cost technique that also allows the patterning of the back side amorphous (a-Si:H) layers on large area IBC-HIT solar cells. However laser irradiation might induce some damage at the c-Si/a-Si:H interface thus limiting the final performance of the devices. In this work, we compare the results obtained with our laser patterning process for different stack configurations and laser ablation conditions (532 nm and 355 nm). We will also discuss about the criteria used for the choice of the different materials and the laser ablation conditions needed in order to successfully pattern both the emitter and BSF (Back Surface Field) regions of the cell. Our best cell efficiency achieved up to now is 20.55% on an area of 18.11 cm 2 .